Frozen II - Buck, Chris; Lee, Jennifer, (Screenwriter); Del Vecho, Peter; Bell, Kristen, 1980-; Menzel, Idina; Groff, Jonathan; Gad, Josh, 1981-; Fontana, Santino; Molina, Alfred, 1953-; Plimpton, Martha, 1970-; Ritter, Jason, 1980-; Wood, Evan Rachel, 1987-; et al. (Burbank, CA : Walt Disney Studios Home Entertainment, 2020)
Anna, Elsa, Kristoff, Olaf, and Sven leave Arendelle to travel to an ancient, autumn-bound forest of an enchanted land. They set out to find the origin of Elsa's powers in order to save their kingdom.
Title from disc surface.
Originally released as a motion picture in 2019.
Wide screen (2.39:1)
Kristen Bell, Idina Menzel, Jonathan Groff, Josh Gad, Santino Fontana, Alfred Molina, Martha Plimpton, Jason Ritter, Evan Rachel Wood, Sterling K. Brown, Rachel Matthews.
Rating: PG; for action/peril and some thematic elements.
DVD, wide screen (2.39:1) presentation; 5.1 Dolby, DVS 2.0 Dolby; described video.
Keywords: Princesses -- Juvenile films; Sisters -- Juvenile films; Magic -- Juvenile films; Adventure and adventurers -- Juvenile films; Quests (Expeditions) -- Juvenile films; Adventure and adventurers; Magic; Sisters; Children's films; Juvenile works; Fiction films; Children's films; Action and adventure films; Feature films; Fantasy films; Animated films